The making of the transitional citizen and the failure of pedagogy - Spajić-Vrkaš, Vedrana (Array, 2013)
In the paper we argue that contemporary pedagogy has failed to respond to one of the most crucial challenges of the transitional societies – the preparation of students as democratic citizens. It has ignored the fact that students are, inter alia, political subjects and that educational decisions are, inter alia, the outcomes of competing political interests. Dependence on the positivist myth of a value-free science has, in time of deep and complex changes through which education is being turned into the market of competing local, national and global interests, made pedagogy irrelevant for maintaining the very essence of education and, thus, co-responsible for the waste of the transitional societies’ human resources. The arguments are based on the results of a pilot-study conducted in seven countries in South-Eastern Europe on the sample of 1594 secondary school students, in which three categories of data were collected. The knowledge dimension encompassed a set of questions on democracy, human rights and citizenship in the context of globalization, Europeanization and pluralisation ; the second dimension included attitudes and opinions about school subject in which citizenship education was taught, and the third dimension comprised of questions relating to civic and political culture. The results confirm that, in all the countries in the region, secondary school students lack knowledge, skills and attitudes for active participation. Weakened by constant political pressure and assisted by no theoretical-normative framework based on empirical and critical discourses, their schools have failed to equip them with tools which are necessary for them to become political subjects who would be able and willing to responsibly contribute to their societies’ democratic development and, through it, to their own wellbeing.